PENGARUH MODAL PSIKOLOGI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (Studi pada Pegawai BPJS Ketenagakerjaan Kanwil Jateng dan DIY, Semarang I, Semarang II dan Ungaran) - Rina Wulandari, 1342020019 (Jurnal Mahasiswa Pasca Sarjana, 2015)
Target of this research to know psychology capital influence, OCB and motivation to BPJS Labour Kanwil Jateng officer performance and DIY. Pursuant to the mentioned hence this research take title âPengaruh Modal Psikologi Dan Motivasi Kerja Terhadap Kinerja DenganÂ Mediasi Organizational Citizenship Behaviour (OCB) (Study pada Pegawai BPJS Ketenagakerjaan Kanwil Jateng dan DIY, Semarang I, Semarang II dan Ungaran)â. In this research take population entire officer in Environment BPJS Labour Kanwil Jateng and DIY, Ungaran, Semarang I and Semarang II amounting to 114 people. Intake of sample with sampling census technique representing method intake of sampel by taking all existing population. As for sample which is taken in this research equal to 114 responder. Data analysis use doubled linear regression. Pursuant to result of research which have been done by hence can know by psychology capital by parsial have an effect on positive and significant to OCB. Motivation by parsialÂ have an effect on positive and significant to OCB. Capital Psychology by parsialÂ have an effect on positive and significant to officer performance. Motivation by parsial have an effect on positive and significant to officer performance. OCB by parsial have an effect on positive and significant to officer performance Equal to 72% officer performance can be explained by psychology capital, OCB and motivation. While the rest 28% explained by other causes outside psychology capital variable, OCB and motivation. OCB do not psychology capital memediasi and motivation to officer performance. Keyword : psychology capital, motivation, Organizational Citizenship Behavior (OCB) And officer performance.